Nanostructured LaFeO3 Photocathodes with Onset Potentials for the Hydrogen Evolution Reaction Over 1.4 V vs. RHE. Issue 15 (1st January 2019) - Sun, Xin; Tiwari, Devendra; Fermin, David J.
Abstract : The photoelectrochemical properties of phase-pure LaFeO3 (LFO) nanostructured films are investigated upon modification with a thin TiO2 film and Pt nanoparticles as a catalyst. LaFeO3  with crystallite domains in the range of 60 nm are prepared by thermolysis of an ionic-liquid precursor and subsequently deposited onto FTO electrode by spin-coating. Deposition of a TiO2 layer by solution-based methods leads to the formation of a heterojunction, attenuating dark current associated with hole-transfer (water oxidation) at potential above 1.4 V. The LFO/TiO2  heterojunction features photocurrent onset potential for the hydrogen evolution reaction of 1.47 V vs. the reversible hydrogen electrode (RHE), which is one of the most positive values reported for a single absorber. Deposition of Pt nanoparticles at the LFO/TiO2  heterostructure generates a significant increase in the HER photocurrent, although bulk recombination remains an important challenge in these constructs.